Mapping the Cultural Learnability Landscape of Danger. Issue 3 (May 2016) - Clark Barrett, H.; Peterson, Christopher D.; Frankenhuis, Willem E.
Abstract : Cultural transmission is often viewed as a domain‐general process. However, a growing literature suggests that learnability is influenced by content and context. The idea of a learnability landscape is introduced as a way of representing the effects of interacting factors on how easily information is acquired. Extending prior work (Barrett & Broesch, 2012 ), learnability of danger and other properties is compared for animals, artifacts, and foods in the urban American children (ages 4–5) and in the Shuar children in Ecuador (ages 4–9). There is an advantage for acquiring danger information that is strongest for animals and weakest for artifacts in both populations, with culture‐specific variations. The potential of learnability landscapes for assessing biological and cultural influences on cultural transmission is discussed.